Exploring the Effective Model of Teaching English Speaking Practiced at University - Roni La'biran (STAI Hubbulwathan Duri, 2023)
Model applied by the lecturer depends on the student's ability to accept the subjects being taught and the student's ability, so it takes the phases of the model used to influence students to be able to speak English well. The purposes of the research are to discover model of teaching speaking practiced at university, students’ perceptions toward the model, the impact of the model, and kinds of interaction used in model of teaching speaking. The researcher employed qualitative methods for the study. The data resources for the research chosen through random sampling was used lecturer from Bosowa University of Makassar, which also included observation and interviews. The result of this study confirms that the model of teaching speaking practiced in Bosowa university was the mastery learning model. This model can be divided into five phases namely: Orientation, Presentation, Structures Practice, Guided Practice, and Independent Practice. The impacts of speaking model are active responsive such as students active to practice their English, students hard working to practice their speaking such as personality practice and group discussion, students have high motivation to practice their English such as prepare core point of speaking exercises, students have good self –confident such as the students are not shy to practice their English, and student have speaking fluency in practicing speaking. Types of classroom interaction used lectures in teaching speaking are closeness interaction, virtual interaction. The impact of the teaching speaking model is active responses, high student motivation, self-confidence, and speaking fluency.